Depression Severity Mediates the Relationships Between Parenting Styles, Peer-Victimization and Mobile Phone Dependence in Adolescents - He Q; Hu X; Chen Y; Li Y; Zhao Y; Zhou Y; Liu L (Psychology Research and Behavior Management)
Qianqian He,1 Xiaofen Hu,1 Yunzhe Chen,2 Yan Li,1 Yunhan Zhao,1 Yongjie Zhou,2 Liang Liu1 1Clinical Research Center for Mental Disorders, Shanghai Pudong New Area Mental Health Center, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 2Brain Regulation and Mental Rehabilitation Laboratory, Shenzhen Mental Health Center/ Shenzhen Kangning Hospital, Shenzhen, People’s Republic of ChinaCorrespondence: Liang Liu, Clinical Research Center for Mental Disorders, Shanghai Pudong New Area Mental Health Center, School of Medicine, Tongji University, Shanghai, People’s Republic of China, Email goldwalker@163.com Yongjie Zhou, Brain Regulation and Mental Rehabilitation Laboratory, Shenzhen Mental Health Center/ Shenzhen Kangning Hospital, Shenzhen, 518118, People’s Republic of China, Email qingzhu1108@126.comPurpose: Negative parenting styles, peer victimization, and mobile phone dependence (MPD) are prevalent public health problems among adolescents. Parenting styles and peer victimization were reported to affect MPD, but their interaction and the mechanism underlying this association still need to be explored. This study aimed to examine how these factors affect MPD in adolescents with depression.Methods: Data was collected from 2324 participants diagnosed with depression aged 12– 18 years in 11 provinces in China in the cross-sectional study. The scales of Mobile Phone Addiction Index, Patient Health Questionnaire-9, Parental Bonding Instrument, and Multidimensional Peer Victimization were adopted to measure the smartphone dependence, the severity of depressive symptoms, parenting styles, and multiple facets of peer victimization, respectively, for all adolescents. Hierarchical regressions were used to explore the main effect and interaction of parenting styles and peer-victimization on depression and MPD. A structural equation model was constructed to examine the direct and indirect effects of parenting styles and peer-victimization on MPD and the role of depression severity.Results: After controlling for gender, age, education, parental education, the study found that parental overprotection and peer victimization significantly predict higher levels of depression and higher risk of MPD. Parental care significantly predicts lower levels of depression. Higher levels of depression were associated with a higher risk of MPD. Further, depression partially mediated the relationship between parental overprotection, peer victimization, and MPD, and fully mediated the relationship between parental care and MPD. These results showed the pathway how parenting styles and peer victimization affect MPD directly and indirectly.Conclusion: Adolescents who experienced negative parenting styles and peer victimization were prone to develop serious depression, then leading to MPD, providing possible intervention directions by changing parenting styles and avoid peer victimization in depression adolescents with MPD.Keywords: mobile phone dependence, adolescents with depression, parenting styles, peer victimization